Aktivitas antibakteri sabun transparan dengan penambahan ekstrak kulit nanas [Antibacterial activity of transparent soap with addition of pineapple peel extract] - Dewi Fortuna Ayu; Adeline Palma Sari; Yelmira Zalfiatri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
The ability of pineapple peel extract to inhibit Staphylococcus aureus thus it can be applied to a transparent soap. The effect of pineapple peel extract addition in the inhibitory effect on the growth of Staphylococcus aureus bacteria and quality of transparent soap was studied. The study used a complete randomized design with five treatments and three replications. The data was statistically analyzed using ANOVA and continued with DNMRT at the level of 5%. The treatments were different concentrations of pineapple peel extract addition: 0%, 1,5%, 2%, 2,5%, and 3% in the transparent soap. The result showed that the variations of pineapple peel extract addition in the making of the transparent soap significantly affected antibacterial activity, water content, amount of fatty acids, free alkali, pH, foam stability, and sensory test. The selected treatment from this study was 3% addition of pineapple peel extract. Transparent soap from this treatment had 11.47% water content, 35.35% total fatty acid, 0.22% free alkali, 10.07 degree of acidity, 73.30% foam stability, and 26.36 mm antibacterial activity against S. aureus. The descriptive test showed that the transparent soap had hard texture, dark brown color, pineapple flavor, and rather transparent.